Champions for School Health—An NASN Initiative to Increase Vaccine Confidence, Equity, and Uptake in COVID-19 and School-Required Vaccinations: Part 1. (May 2023) - D'Souza-Vazirani, Deborah; Walsh, Carol; Tanner, Andrea L.; Clark, Elizabeth; Griffin, A. Renee; White, Stephanye
The National Association of School Nurses (NASN) received a U.S.2 million grant from Kaiser Permanente in January 2022 to increase confidence, equity, and uptake in the COVID-19 vaccine and other school required vaccinations in children ages 5 to 11 in Kaiser's nine markets (eight states and the District of Columbia). NASN was partnered with the Institute of Educational Leadership (IEL) in this initiative to examine ways both organizations could learn how school nurses (SNs) and community schools (CSs) could collaborate to address the goals of this project. NASN gave 54 Implementation Grants in two funding cycles in 2022 and is co-funding two SN-CS collaboration projects with IEL. The Part 1 article provides an overview of the project's goals, grant strategy and processes, grantee information, NASN created tools that resulted from this funding, and successful implementation of the project, which demonstrates NASN's capacity for future similar projects.